Successful Stone Extraction From The Common Bile Duct By ERCP In A Patient With Situs Inversus Totalis - Ch, Sumera Mushtaq; Murtaza, Ghulam; Fatima, Kiran; Kazmi, Kumail Hasan; Ulhaq, Hidayat; Hussain, Tassawar (Journal of Rawalpindi Medical College, 2026)
ERCP is an invasive procedure for removing common bile duct and pancreatic stones, and the instrument is specially designed for the normal anatomy of intra-abdominal organs. We describe a case of removing CBD stones by ERCP in a patient with situs inversus totalis. ERCP is a challenging procedure most of the time, even with normal anatomical structures, and is more difficult or impossible with situs inversus totalis. CBD was assessed as very difficult by an experienced Gastroenterologist, and stones were successfully removed. ERCP was performed, placing the patient in the prone position with the gastroenterologist standing on the normal left side of the table. The duodenoscope was first rotated 180° counterclockwise in the stomach and then shortened by rotating the scope again to 180° clockwise in the duodenum. For the second technique, we assessed the second portion of the duodenum by following the lesser curvature, while slowly turning the endoscope clockwise. Papillotomy was done in a complicated way, and a stent was successfully placed in the CBD with free flow of bile. Keywords: Situs inversus totalis, Endoscopic retrograde cholangiopancreatography (ERCP), Choledocholithiasis.